A reference model as automated process for software adaptation at runtime - Affonso, Frank Jose [UNESP]; Carneiro, Maria Cecilia Vecchiato Saenz [UNESP]; Rodrigues, Evandro Luis Linhari; Nakagawa, Elisa Yumi (Ieee-inst Electrical Electronics Engineers Inc, 2015)
The development of self-adaptive software (SaS) has specific characteristics compared to traditional one, since it allows that changes to be incorporated at runtime. Automated processes have been used as a feasible solution to conduct the software adaptation at runtime. In parallel, reference model has been used to aggregate knowledge and architectural artifacts, since capture the systems essence of specific domains. However, there is currently no reference model based on reflection for the development of SaS. Thus, the main contribution of this paper is to present a reference model based on reflection for development of SaS that have a need to adapt at runtime. To present the applicability of this model, a case study was conducted and good perspective to efficiently contribute to the area of SaS has been obtained.
Keywords: Automated Process; Reference Model; Runtime; Self-adaptive Software